(untitled) (Olhar de Professor, 2024)
This article aimed at outlining an enunciative-discursive path of linguistic/semiotic analysis practices (Prática de Análise Linguística/Semiótica, PAL/S) developed during Portuguese language curricular component classes. To do so, the theoretical basis is constituted by discussions involving linguistic/semiotic analysis practices and Portuguese language teaching in basic education, specifically in the first grades of Elementary School, in a dialogue with National Curriculum Parameters (Parâmetros Curriculares Nacionais, PCN) and National Common Curricular Base (Base Nacional Comum Curricular, BNCC). A theoretical review was developed about the subject of study, so it would be possible to stablish approximations between researches involving PAL/S and the forementioned parameterizing documents in the light of dialogical perspective. It is understood that, in parameterizing documents, there are centripetal forces considering the existance of tradition discourses, as well as centrifugal forces that propose an enunciative-discursive teaching focusing on reading, writing/speaking and linguistic/semiotic analysis practices.